The Relation between Lifestyle and Nutritional Status of Adolescents in Central Jakarta - Fatimah, Nurul; Linda, Ony; Trimawartinah, T (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: The purpose of this study was to determine the relation between lifestyle with nutritional status of adolescent in Central JakartaMethodology: This research is quantitative with a cross sectional design. The research population was 268 adolescents with a sample of 135 adolescents. Samples were taken using probability sampling technique with proportionate random sampling. The dependent variable in this study was nutritional status and the independent variable in this study was lifestyle including physical activity, smoking behavior, and sleep duration.Results: The results of univariate analysis in this study showed that 54.8% of adolescents had poor nutritional status, 61.5% of adolescents had mild physical activity, 78.5% of adolescents had no smoking behavior, and 63.0% of adolescents had a good sleep duration. The results of the chi square statistical test showed that there was a relation between physical activity (pvalue = 0.004) and sleep duration (pvalue = <0.0001) while there was no relation between smoking behavior (pvalue = 0.799) and nutritional status.Applications/Originality/Value: This manuscript is an original work that has never been published or published in other media.